10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Preoperative anxiety, sleep disturbances and postoperative delirium are common complications among patients undergoing cardiac surgery and are associated with adverse perioperative outcomes. This scoping review aimed to synthesise evidence on the relationship between these factors and identify implications for perianaesthesia nursing practice. A literature search was conducted in PubMed, Scopus and Web of Science for studies published between 2016 and 2026. Twenty-five studies met the inclusion criteria. The findings indicated that preoperative anxiety and poor sleep quality were consistently associated with an increased risk of postoperative delirium. Several studies also reported beneficial effects of educational, psychosocial and sleep-focused nursing interventions on perioperative outcomes. The evidence suggests that anxiety, sleep disturbances and delirium are interrelated and potentially modifiable risk factors. Integrating psychological assessment, sleep evaluation and routine delirium screening may support earlier identification of high-risk patients and improve postoperative recovery.